The Choice of Optimal Treatment Methods for Invaginal Intestinal Obstruction in Children - K.S, Yulchiev; .K. Z, Kadirov (Journal of Neonatal Surgery, 2025)
Annotation: The experience of treatment of 75 patients with various variants of invagination intestinal obstruction (IIO) in children was analyzed. The structure and methods of treatment (IIO) at different stages of the disease are presented.There were 31(41.3%) patients admitted to the hospital up to 12 hours after the onset of the disease. In these patients, the invaginate was tried to be disinvaginated conservatively. At the same time, 12 patients managed to disinvaginate conservatively, while the remaining 19 patients failed. Out of the total number of 63 (100%) operated patients, 17 (27%) patients underwent minimally invasive laparoscopic disinvagination. In 8 (13%) patients, it was possible to disinvaginate, and in 9 (14%) patients, due to technical impossibility, they switched to conversion. In 55 (73.3%) patients, the operation was performed by laparotomic (right pararectal) access. In 52 patients, intestinal intussusception was disinvaginated. In 3 cases, a right-sided hemicolectomy was performed with partial resection of the small intestine and subsequent (second stage)- ileotransverzoanastomosis. All patients were discharged with recovery. One patient died, it was a child, 6 months old with acute intestinal intussusception, many days ago, complicated by peritonitis on the background of multiple organ failure syndrome. In our opinion, there should be an individual approach to each patient with this disease, both in the treatment tactics and in the administration before and after the operating period. Each of the selected treatment methods has its own indications and a reasonable approach to a particular type of treatment. Based on our own material, we analyzed the results of treatment and proposed the most rational approach to the diagnosis and treatment of intestinal intussusception. Therapeutic tactics for complicated forms of intestinal intussusception were based on the effectiveness of lymphotropic and antibacterial therapy for severe inflammatory processes in the intestine..